Políticas culturais e patrimônio histórico : o processo de tombamento do setor histórico da Lapa/PR como estudo de caso - Machado, Alisson Bertão (2007)
This research has as objective to analyze the process of declarations of the Historical Sector of Lapa as a public patrimony in the period from 1979 to 1989, when a series of impediments were presented as objections for the maintenance of an area of the city, considered by the official politician as a historical sector deserving preservation for the present and future people. I present the constructions of the patrimony category, the changes in the time and in the space that the concept has suffered until acquire the actual connotation. I work with the historical process of definition of a institutional politic for the cultural patrimony in Brazil and in the state of Paraná, in a way to comprehend as the practices of preservation of the cultural patrimony. I demonstrate the conflicts which involved the local preservationist decisions, in a way to show the plurality of values, such as economical, cultural and historical, which confronted, in the analyzes period, individual and collective interests. The occurred actions during the process of the Historical Sector of Lapa as a public patrimony allowed me to contextualize the patrimony in the social process which is used to maintain it and they contributed, as well, to the understanding of the sense of the construction of patrimonial images.